Spoilage bacteria in ewe milk and the sheep dairy farm environment : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science/Microbiology at Massey University, Manawatū, New Zealand - Risson, Alexis (Massey University, 2023)
Milk spoilage bacteria are capable of impacting the stability, processability, and overall quality of dairy products. These contaminants are highly diverse and can be found at various stages of the dairy production, but the majority originate from the dairy farm environment where they contaminate raw milk. On bovine dairy farms, research has identified several routes of transmission of spoilage microorganisms into raw milk, as well as some of the factors that modulate this process. This knowledge has aided the design, development and implementation of interventions aiming to limit the on-farm contamination of raw milk and thereby improve the microbiological quality of cow dairy products. In contrast, the microbial communities associated with the ovine dairy production have been largely overlooked. This lack of understanding of the ecology and transmission of spoilage bacteria on sheep dairy farms and in dairy products hinders attempts at reducing the farm-borne contamination of ewe milk by spoilage organisms. In this thesis, I set out to identify and characterise the microbial communities associated with the ovine dairy production, with a focus on bacteria capable of impacting ewe milk quality. In the first part, I compiled, developed, and subsequently used an extensive set of culture methods targeting the main types of bacteria implicated in dairy spoilage, namely spore-forming bacteria, and Pseudomonas species. These methods were applied to survey the microbial communities present in the farm environment of dairy ewes that were grazed or housed. For the first time, this approach provides a detailed overview of the ecology of spoilage bacteria found on sheep dairy farms and enables the identification of numerous bacterial species with spoilage potential. The diversity and principal reservoirs of spoilage bacteria were found to vary between the two farms, possibly as a result of their farming practices. In the second part, I performed source-tracking of the contaminants isolated from milking cups using phylogenetic tools such as DNA fingerprinting and whole-genome sequencing. According to this approach, sources of milking cup, and thus possibly raw milk contamination were found to vary between the two farms. In the barn environment, the silage-faeces axis was identified as the main source of spoilage bacteria in the wider farm environment and in milking cups. There was also some contribution, albeit minimal, from bedding materials and animal drinking water as potential intermediaries. In the pasture environment, the transmission of bacteria in the environment was low, but the origin of the contaminants found in milking cups was multiple, dependent on the bacteria considered, and included soil, pasture, animal faeces and drinking water. In addition, the phylogeny of Thermoactinomyces spp., which were found to be particularly abundant in both housing and grazing environments, was studied in more depth using whole-genome sequencing. Finally, I surveyed the microbiological quality of ewe raw milk samples and sheep dairy products produced in New Zealand using the culture methodology developed for the farm studies. This work provided a glimpse of the diversity and abundance of the spoilage microbiota of sheep milk and dairy products produced in New Zealand. It was found that the microbiological quality of sheep dairy products was high, however, the presence of a highly diverse range of spoilage bacteria highlights their potential to impact the quality of a variety of dairy products.
Keywords: microbiology, dairy, quality, spoilage bacteria, bacterial spores, spore-formers, Pseudomonas, sheep, farm, environment, genetic relatedness, phylogeny; Sporeforming bacteria; Pseudomonas; Molecular aspects; Sheep milk; Microbiology; Milk contamination; Dairying; 310701 Bacteriology